2016
DOI: 10.5423/ppj.oa.12.2015.0263
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Homologous Recombination-Based Gene Manipulation in the Rice Pathogen Fusarium fujikuroi

Abstract: Gene disruption by homologous recombination is widely used to investigate and analyze the function of genes in Fusarium fujikuroi, a fungus that causes bakanae disease and root rot symptoms in rice. To generate gene deletion constructs, the use of conventional cloning methods, which rely on restriction enzymes and ligases, has had limited success due to a lack of unique restriction enzyme sites. Although strategies that avoid the use of restriction enzymes have been employed to overcome this issue, these metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…Pathogenicity was assessed by plant height in the present study. It has been reported that fumonisin producers do not induce the typical symptoms induced by gibberellin in rice, such as stem elongation, but instead cause root rot and stunting (24,34). Gene disruption of Fusarium cyclin C1 (FCC1) or FUM1, which play an important role in fumonisin biosynthesis in the fumonisin-producing strain B14, resulted in a significant reduction in stunting-type symptoms (24,35).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenicity was assessed by plant height in the present study. It has been reported that fumonisin producers do not induce the typical symptoms induced by gibberellin in rice, such as stem elongation, but instead cause root rot and stunting (24,34). Gene disruption of Fusarium cyclin C1 (FCC1) or FUM1, which play an important role in fumonisin biosynthesis in the fumonisin-producing strain B14, resulted in a significant reduction in stunting-type symptoms (24,35).…”
Section: Discussionmentioning
confidence: 99%
“…30 The Fusarium cyclin C1 gene (fcc1) was first chosen as the target gene, because previous research has demonstrated that fcc1-disrupted F. f ujikuroi strains exhibited significantly more red pigment accumulation on PDA compared with the control. 25 In order to verify whether this phenomenon is also present in our strain, we constructed an fcc1-disruption cassette and disrupted the fcc1 gene via homologous recombination (Figure 3). Interestingly, when grown on PDA, the fcc1-disrupted F. fujikuroi accumulated more purple pigment rather than red (Figure 3).…”
Section: Modification Of the Protoplast-based Polyethylenementioning
confidence: 95%
“…This vector was used to disrupt the gene encoding P450-3 , thus yielding the final disruption mutant Δ P450-3 . Subsequently, sgRNA and f FuCas9 vector were introduced into F. fujikuroi through the modified protoplast-based polyethylene glycol and Ca 2+ transformation method ( Hwang and Ahn, 2016 ). Additionally, overexpression of two key genes encoding copalyl diphosphate synthase/kaurene synthase ( Cps/Ks ) and a truncated HMG-CoA reductase ( tHmgR ) were also performed separately and simultaneously to explore the possibility of increasing the amount of GA4/GA7 mixture produced based on previous research ( Albermann et al, 2013 ).…”
Section: Specific Application Of Crispr/cas9 In Secondary Metabolitesmentioning
confidence: 99%